تحليل موادي كتاب المدرسي في كتاب العرطي تأليف شيخ الشريف الدين يحي العمرطي رحمه الله - Amania, Januari (Yayasan Haiah Nusratul Islam, Indonesia, 2024)
Textbooks are all forms of materials used to assist teachers when carrying out classroom activities. Not all schools have the opportunity to get enough textbooks, both in quality and in quantity. The acquisition of textbooks in schools is still limited to the allocation of funds.As for the research questions in this research 1. What is the Book of Arti 2. How to present the material in the book Al-Murrasi Al-Arti written by Sheikh Sharif Al-Din Yahya Al-Amrati - may God have mercy on him 3.What are the advantages and disadvantages in the book Al-Murrasi Al-Arti written by Sheikh Sharaf Al-Din Yahya Al-Amrti. Research Objectives 1. To know the planets Arti - may God have mercy on him 2. To know the presentation of the material in the book of the arti school according to Sheikh Sharif al-Din Yahya al-Amrti - may God have mercy on him 3. To know the advantages and disadvantages in the book of the arti school written by Sheikh Sharaf al-Din Yahya al-Amrti - may God have mercy on him. The type of research used in this research is a type of library research (library research). It is the data that will be retrieved based on documents that are in the form of notebooks, journals, scientific and so on. This research is both descriptive analysis, and then described as what it is, according to the results of the research.